Determining a Relationship in the Nature of Marriage: The Impact of Ruka on the Department of Work and Income’s Conjugal Status Policy - Wiseman, Jessica (Victoria University of Wellington Law Review, 2001)
In the 1997 case of Ruka v Department of Social Welfare, the Court of Appeal altered the test for determining whether a relationship was "in the nature of marriage" for the purposes of the Social Security Act 1964. In this article, the author analyses the impact of the decision on Department of Work and Incomes practice and on the subsequent decisions of the Social Security Appeal Authority. The author questions whether either Department or Appeal Authority has significantly altered their policy in light of the test adopted by the majority in Ruka. In light of its practical application, the author then critically accesses the test in Ruka and concludes that the general approach favoured by previous decisions of the High Court, and apparently continued by the Department subsequent to Ruka, is preferable.